Performance measurements of oil palm stem as potential raw material in certified plywood production - Adnan, Aida; Md. Tahir, Paridah; Saleh, Rosli; Mohd Noor, Khamuruddin (Indonesian Wood Research Society, 2014)
Timber certification has becoming an important and growing phenomenon in forestry sector all over the world. It is generally regarded as a measurement stick for a company to show commitment towards the efforts of implementing well managed forest. Two certification schemes used in Malaysia, Forest Stewardship Council (FSC) and Programme for the Endorsement of Forest Certification (PEFC)¹. Oil Palm Stem (OPS), a nonwood material, including residues from oil palm plantations, was considered as an alternative raw material source for certified product with the fact that it is much cheaper than wood. In certification, OPS is categorised as “neutral material” under the PEFC and “non-forest base material” by FSC whereby it is not included in the calculation of certified wood content in certified product. The main objective of the study was to assess OPS plywood performance using “Property-Cost Index (PCI)” as a measurement tool. The study proven that the properties of OPS plywood produced can perform significantly better, provided that the OPS veneer undergone a resin pre-treatment after veneer drying. PCI result shows that the production of OPS plywood (with resin pre-treatment) is better (1.76) than plywood produced using 100% wood as raw material (1.57).